Perijinan Pembangunan Kawasan Dalam Penataan Ruang - B. Kombaitan (The Institute for Research and Community Services, Institut Teknologi Bandung, 1995)
Developments permit of a zone in various stages related to the last two scopes of spatial planning, spatial use and control in spatial use. This article review some example of development permits recognized today, after explaining the position of permit in spatial planning. As an illustration, an example of a permit procedure in industrial zone is given. On the basis of the illustration, the correlation between the permit issue with the spatial planning is shown. The correlation between various hierarchical spatial planning product and environmental study or plan with hierarchical permit issue, will be the main focus of this article. So, this hierarchical correlation is still not well recognized, so that through this understanding it is mode full that spatial planning can be made more effective. It is also hopeful that this review can enhance public participation in spatial planning.